Refinement of uml collaborations - Hnatkowska, Bogumiła; Huzar, Zbigniew; Tuzinkiewicz, Lech (Zielona Góra: Uniwersytet Zielonogórski)
The paper concerns the concept of refinement as a commonly used design practice in the software development process.The refinement relationship is formulated and formally expressed for UML collaborations. Collaborations are suitable forpresenting the proposed approach as they represent both static and dynamic aspects of a modeled system or its part, forexample, a use case. Our approach to refinement is based on the rule of preserving the observable behavior of a modeledsystem. The introduced notion of sub-collaborations allows us to refine collaboration diagrams in a systematic way.
Keywords: UML; collaborations; refinement